Volume 4: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27167
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Study of Heat Transfer and Pressure Losses of V- and W-Shaped Ribs at High Reynolds Numbers

Abstract: An experimental and numerical investigation was conducted to assess the thermal performance of V- and W-shaped ribs in a rectangular channel. The ribs were located on one channel sidewall in order to simulate a typical combustor liner cooling. The cross section of the channel had an aspect ratio of 2:1. Local heat transfer coefficients were measured using the transient thermochromic liquid crystal technique. Pressure taps along the channel sidewall were used to obtain the periodic pressure losses. The rib heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
3
19
1
Order By: Relevance
“…CENTAUR ® software [52] (see also Sect. 8.2) confirmed also by [16,57], etc. A grid-independency investigation carried out using a coarse mesh of *1.1 million cells, a medium mesh of 1.9 million cells, a finer mesh of 3.2 million cells, and a very fine mesh of 3.65 million to 3.91 million cells revealed that namely the very fine mesh ensured the sufficient near-wall grid resolution and grid independency for the ribbed channel, while for the smooth channel a grid with 1.15-1.3 million cells was needed.…”
Section: Numerical Methodologysupporting
confidence: 73%
See 1 more Smart Citation
“…CENTAUR ® software [52] (see also Sect. 8.2) confirmed also by [16,57], etc. A grid-independency investigation carried out using a coarse mesh of *1.1 million cells, a medium mesh of 1.9 million cells, a finer mesh of 3.2 million cells, and a very fine mesh of 3.65 million to 3.91 million cells revealed that namely the very fine mesh ensured the sufficient near-wall grid resolution and grid independency for the ribbed channel, while for the smooth channel a grid with 1.15-1.3 million cells was needed.…”
Section: Numerical Methodologysupporting
confidence: 73%
“…In experiments [57] on a rough disk, the onset of transition to turbulence began at Re ω = (0.23-1.23) × 10 5 (on a smooth disk, at Re ω = (2.4-2.63 × 10 5 ). The boundary of the end of transition also shifted down to Re ω = 2.55 × 10 5 on a rough disk in comparison with Re ω = 3.4 × 10 5 on the smooth disk in [58].…”
Section: Transition To Turbulent Flowmentioning
confidence: 99%
“…The overall thermal performance was found to be better for the discrete V-shaped and discrete W-shaped ribs in comparison to continuous V-and Wshaped ribs. Maurer et al [86] investigated the thermal performance of V-shaped and W-shaped ribs provided on one side or both sides of a test channel for an Re range of 80,000e500,000. The W-shaped ribs were found to have better heat transfer and pressure drop.…”
Section: Baffles Used As Roughness Turbulence Promoters In Solar Air mentioning
confidence: 99%
“…V-shaped ribs show a higher thermal performance than angled ribs. Similar comparative analysis was conducted by [9] experimentally and numerically to examine the thermal performance of V-shaped and W-shaped ribs in a rectangular channel with an aspect ratio of 2:1. The blockage ratio (e/D h ) was 0.02; the rib pitch-to-height ratios (P/e) were 5 and 10 and the tests were performed for Reynolds numbers between 80,000 to 500,000.…”
Section: B Ribs On One Side Of the Channel -mentioning
confidence: 99%